Rationality + consciousness = free will - Hodgson, David (Philosophy of mind series., 2012)
In recent years, philosophical discussions of free will have focused largely on whether or not free will is compatible with determinism. In this challenging book, David Hodgson takes a fresh approach to the question of free will, contending that close consideration of human rationality and human consciousness shows that together they give us free will, in a robust and indeterministic sense. In particular, they give us the capacity to respond appositely to feature-rich gestalts of conscious experiences, in ways that are not wholly determined by laws of nature or computational rules. The author contends that this approach is consistent with what science tells us about the world; and he considers its implications for our responsibility for our own conduct, for the role of retribution in criminal punishment, and for the place of human beings in the wider scheme of things.